2016
DOI: 10.1080/13676261.2015.1136055
|View full text |Cite
|
Sign up to set email alerts
|

Transition to adulthood and recession: a qualitative study

Abstract: While the transition to adulthood has been broadly examined, less is\ud known about the impact of economic recession on the well-being\ud and psychosocial functioning of young people. The present study\ud used qualitative interviews with 12 college students to understand\ud their experience. Consensual qualitative research was used to\ud analyse data and develop core themes around young people’s\ud experiences. Interviews focused on how young people perceived\ud the impact of the economic recession on their so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
1
13
0
2
Order By: Relevance
“…It was only the classification that was used from the method described in Hill et al (2005) . This classification was used in a similar way in Regev et al (2016) and Di Blasi et al (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…It was only the classification that was used from the method described in Hill et al (2005) . This classification was used in a similar way in Regev et al (2016) and Di Blasi et al (2016) .…”
Section: Methodsmentioning
confidence: 99%
“…The transition from school to work can be influenced by macroeconomic factors such as recession also among young people who are not in NEET. A qualitative study of students [14] showed that the crisis had negative impact on the participants’ mental health by creating feelings of instability as well as difficulties in planning for the future.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to the variables tested in the present study, future studies should consider their interaction with other factors, such personality traits close to SA (e.g., shyness, introversion) and psychiatric disorders such as major depressive disorder panic disorder, posttraumatic stress disorder that are the most frequent principal diagnosis in patients with comorbid SAD ( 5 , 57 ). Socio-economics factors could also play a potential role since recent literature indicate that during the last decade recession hardships increase psychological distress ( 58 , 59 ) which in turn increases marijuana and other illicit drugs use ( 60 ). Additionally, as recent studies highlighted that high-potency and synthetic cannabinoids compared with the use of natural cannabis, may cause more frequent and more severe unwanted negative effects such as agitation, paranoia, psychosis ( 61 , 62 ), further studies should be conducted to consider the influence of type of cannabis smoked on the SA symptoms.…”
Section: Discussionmentioning
confidence: 99%